International Iron Sculpture Symposium Yahata '87. (Yahata : Yahata City, 1987)
Abe, Momoru ; Bori, Kiyonori ; Hukudo, Atsuo ; King, Philip ; Mach, David ; Muraoka, Saburo ; Nakanishi, Hisayoshi ; Nishi, Masaaki ; Sukenari, Masanori ; Takayama, Noboru
International Iron Sculpture Symposium Yahata '87, Yahata City, 1987.10.10 - 11.15
Japans
kunstcatalogus